Compliance Gaining in Communication Between Mursyid Teachers and Their Students - Mukarromah; Pawito; Albert Muhammad Isrun Naini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study describes the communication of obedience between murshid teachers and their students. This research is a strategy by Maulana Habib Luthfi Bin Yahya, an Indonesian murshid teacher, to persuade his students to comply with Islamic orders and laws. This article looks at how his processes and efforts during preaching earned such high obedience from his students. This study uses a qualitative descriptive approach and the theory of Compliance Gaining Marwell & Schmitt. Based on the research results, it is known that Habib Luthi bin Muhammad Bin Yahya does not have a specific strategy for obtaining absolute compliance and compliance does not always have to start with an appropriate process. The main focus is on personal commitments.